Application of Projected Unit Credit Method and Entry Age Normal in Pension Fund Insurance of PT Pos Indonesia, South Aceh Regency - Sholahuddin Al Ayubi, Faqih; Victorio Rudolfo Purba, Daniel (Communication In Research And Publications, 2024)
This study aims to analyze the application of the Projected Unit Credit (PUC) Method and the Entry Age Normal (EAN) Method in the context of pension fund insurance. The Projected Unit Credit Method and the Entry Age Normal Method are two actuarial approaches used to calculate liabilities and determine the required contributions in pension plans. The Projected Unit Credit Method calculates based on projected future salaries and benefits accumulated over the employee's working life, while the Entry Age Normal Method distributes the cost of retirement benefits evenly over the employee's working life. Data was collected from various pension plans that use both methods. Analysis was conducted to compare the accuracy of liability estimation, contribution stability, and the impact of each method on pension fund sustainability. The results show that the Projected Unit Credit Method provides a more realistic liability estimate by considering salary increases, while the Entry Age Normal Method offers better contribution stability from year to year. The selection of the appropriate actuarial method is highly dependent on the objectives and specific conditions of the pension program being managed. These findings are expected to help pension fund managers make more informed decisions to ensure the welfare of pension plan participants.